1999
DOI: 10.1002/(sici)1521-4036(199906)41:3<321::aid-bimj321>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Robust One-Way ANOVA under Possibly Non-Regular Conditions

Abstract: Consider the one-way ANOVA problem of comparing the meansSolutions are available based on (i) normal-theory procedures, (ii) linear rank statistics and (iii) M-estimators.The above model presupposes thathave equal variances ( homoscedasticity). However practising statisticans content that homoscedasticity is often violated in practice. Hence a more realistic problem to consider iswhere F is symmetric about the origin and s 1 Y F F F Y s c are unknown and possibly unequal ( heteroscedasticity). Now we have to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 33 publications
(28 reference statements)
0
16
0
Order By: Relevance
“…2.1. Babu et al's (1999) procedure Consider the problem of comparing distributions F 1 ¼ F 2 ¼ · · · ¼ F J : One way of approaching this problem is to consider the one-way ANOVA problem of comparing means m 1 ¼ m 2 ¼ · · · ¼ m J from J distributions F 1 ð yÞ ¼ Fð y 2 m 1 Þ; F 2 ð yÞ ¼ Fð y 2 m 2 Þ; : : : ; F J ð yÞ ¼ Fð y 2 m J Þ: When the distributions are unknown and one cannot assume that they are normal with equal variances, Babu et al (1999) suggested the following procedure:…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…2.1. Babu et al's (1999) procedure Consider the problem of comparing distributions F 1 ¼ F 2 ¼ · · · ¼ F J : One way of approaching this problem is to consider the one-way ANOVA problem of comparing means m 1 ¼ m 2 ¼ · · · ¼ m J from J distributions F 1 ð yÞ ¼ Fð y 2 m 1 Þ; F 2 ð yÞ ¼ Fð y 2 m 2 Þ; : : : ; F J ð yÞ ¼ Fð y 2 m J Þ: When the distributions are unknown and one cannot assume that they are normal with equal variances, Babu et al (1999) suggested the following procedure:…”
Section: Methodsmentioning
confidence: 99%
“…In addition, other authors have developed procedures that use other measures of central tendency-e.g. sample medians-to assess the effects of a treatment variable across groups (see Babu, Padmanabhan, & Puri, 1999;Wilcox & Keselman, 2003a, 2003b. Keselman (2003a, 2003b) introduced a modified one-step M (MOM) estimator which empirically determines whether to trim symmetrically or asymmetrically and by what amount, or whether no trimming at all is appropriate.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In view of these findings, extreme outliers that fell more than three standard deviations from the group mean were replaced with the next extreme plus one (four data points; one case in each condition) (Tabachnick and Fidell, 2001). The main analyses were a series of one-way analyses of variance (ANOVAs) conducted on this dataset (Glass et al, 1972;Lix et al, 1996;Babu et al, 1999;Tabachnick and Fidell, 2001).…”
Section: Data Processingmentioning
confidence: 99%